TOXICOLOGY TEST ON COAL ASH FROM ASAM-ASAM COAL FIRED POWER PLANT, TANAH LAUT - SOUTH KALIMANTAN - SITI R. UNTUNG (Indonesian Mining Journal, 2011)
The utilization of coal at Asam-asam Coal Fired Power Plant produces a by-product of ash waste that consists of either coal ash or bottom ash. The power plant produces 720 tons of coal ash each year that threatens the environment due to pollution to surrounding waters. Based on the Government Regulation No. 85/1999, coal produces hazardous and toxic wastes. Due to that situation, toxicology test has been con- ducted on coal ash using Cyprinus carpio L. The research also analyzed chemical composition of the ash, Toxicity Characteristic Leaching Procedure (TLCP) test as well as determined the acute characteristic by setting Lethal Concentration 50 (LC50). Chemical analysis shows that the almost 90% of coal ash and bottom ash are comprise SiO2, Al2O3, and Fe2O3. The TCLP test using atomic absorption spectrophotometer shows that heavy metals with in the coal ash filtrate were Pb (3.1 ppm), Zn (4.3 ppm), Cd (0.2 ppm), Cu (2.2 ppm), but As and Cr were not detected; in the bottom ash. there were Zn (3.1 ppm), Cu (0.2 ppm), while Pb, Cd, As and Cr were not detected. It suggests that the power plant heavy metals with in the coal ash was still the quality standard as regulated by the Government Decree No. 85/1999 and US EPA. Therefore the coal ash is not categorized as hazardous and poisonous waste. Moreover, the result of acute toxicity test conducted by examining the number of dead fish, shows that the LC concentration values of fly ash and bottom ash are 20.564% (205,640 ppm) and 11.637% (116,370 ppm). Referring to the Association of Australian Petroleum Energy criteria of LC50 toxicity, the coal ash from Asam-asam is a non toxic waste.